Phenotypical categorization of indigenous ewes as resistant, resilient or susceptible to Haemonchus contortus - DAVID,CAROLINE M.G. (2022)
Abstract The economic losses caused by parasite infections, aggravated by resistance to anthelmintics, have generated demand for alternatives involving non-chemical control, such as the selection of resistant animals. The objective of this study was to identify which characteristics best describe animals that are resistant, resilient or susceptible to Haemonchus contortus and estimate the percent number in each category. Sixty-one Morada Nova ewes were evaluated in an extensive system. The performance variables (weight, body condition score), hematological variables (packed cell volume, hemoglobin, white blood cells, segmented neutrophils, lymphocytes, eosinophils, monocytes) and fecal egg counts were measured individually every 14 days during 6 months. The variables were transformed, and analysis of variance was carried out, with construction of a correlation network. Characteristics linked to parasite infection showed variations among the categories, which helped to identify sheep resistant, resilient or susceptible to H. contortus. Based on the analyses performed, 88.3% of the animals were resistant or resilient and only 11.7% were susceptible. Presence of Trichostrongylidae eggs, body condition score, packed cell volume (PCV) and eosinophil counts were found to be good indicators of naturally infected ewes, and there were significant differences between the categories and correlations between the traits.